THE EFFECT OF DENTAL HEALTH EDUCATION USING MUSIC IN DECREASING PLAQUE INDEX OF INTELLECTUALLY DISABLED - Shaula Chintyasari; Isnur Hatta; I Wayan Arya Krishnawan Firdaus (Dentino : Jurnal Kedokteran Gigi, 2020)
Background: Intellectually disabled (ID) children refer to special needs children whose intelligences are below the average. Poor dental and oral health conditions are a problem that is often found in ID children. Dental health education (DHE) on toothbrushing activity for ID children can be a solution for their dental and oral health problems, however ID children have limitation in receiving information caused by the deficit of cognitive functions covering perception, memory, idea development, evaluation, and reasoning. Effective learning processes in DHE for ID children can be achieved by using adaptive media like music adjusted to the condition of ID children. Objective: To analyze the effect of DHE using music in decreasing plaque index of mild-to-moderate ID children. Methods: Pre-experimental (one-group pre and posttest) and total sampling method were used. Thirty subjects, junior high school students with mild-to-moderate intellectual disability (9 females and 21 males), were given 15 sessions of DHE using music as adaptive media. The music was in the form of children's song, which contains stages of tooth-brushing using modified-bass technique, created specifically by adjusting to characteristics of ID children. Plaque index was measured using Quigley–Hein Turesky–Gilmore–Glickman modification on day-0, 3, 6, 9, 12, and 15. Results: Average plaque index of all subjects (mean±SD): pretest (4.79±0.27), posttest-1 (4.37±0.36), posttest-2 (4.02±0.42), posttest-3 (3.39±0.46), posttest-4 (2.78±0.65), posttest-5 (2.29±0.86), Wilcoxon statistical analysis showed that there are significant differences (p<0,05). Conclusion: DHE using music as adaptive media in the form of children's songs can affect the reduction in plaque index of mild-to-moderate ID children since the 3rd day. The decrease in male subjects' plaque index was slower than in female subjects. Grade level does not affect the decrease in plaque index of ID children. Lingual surface’s plaque index had higher score with slower decline than buccal surface.